2017
DOI: 10.1038/srep45457
|View full text |Cite
|
Sign up to set email alerts
|

Study on the short-term effects of increased alcohol and cigarette consumption in healthy young men’s seminal quality

Abstract: Many studies have reported a negative impact of lifestyle factors on testicular function, spermatozoa parameters and pituitary-gonadal axis. However, conclusions are difficult to draw, since studies in the general population are rare. In this study we intended to address the early and late short-term impact of acute lifestyle alterations on young men’s reproductive function. Thirty-six healthy male students, who attended the Portuguese academic festivities, provided semen samples and answered questionnaires at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
0
14
0
3
Order By: Relevance
“…In patients with high BMI (>28 kg/m 2 ) compared with normal BMI, increased reactive oxygen species (ROS) activity in semen and sperm DNA fragmentation were found,these are factors linked to poorer sperm quality that may account for poorer IVF treatment outcomes 48,49. STL attrition is linked to ROS exposure in relation to environmental and lifestyle factors such as alcohol consumption and smoking [50][51][52]. However, Mishra and colleagues demonstrated that a mild increase in oxidative stress is beneficial for STL maintenance 53.…”
mentioning
confidence: 99%
“…In patients with high BMI (>28 kg/m 2 ) compared with normal BMI, increased reactive oxygen species (ROS) activity in semen and sperm DNA fragmentation were found,these are factors linked to poorer sperm quality that may account for poorer IVF treatment outcomes 48,49. STL attrition is linked to ROS exposure in relation to environmental and lifestyle factors such as alcohol consumption and smoking [50][51][52]. However, Mishra and colleagues demonstrated that a mild increase in oxidative stress is beneficial for STL maintenance 53.…”
mentioning
confidence: 99%
“…We observed that semen quality is also affected by alcohol consumption, represented by lower semen volume, sperm concentration, motility and normal morphology. Previous studies have suggested a negative association between alcohol consumption and semen quality (Gaur, Talekar, & Pathak, ; Joo et al, ; Martini et al, ; Muthusami & Chinnaswamy, ; Silva et al, ; Stutz et al, ), although others did not confirm these findings (de Jong, Menkveld, Lens, Nienhuis, & Rhemrev, ; Hansen et al, ; Jensen et al, ; Lopez Teijon et al, ). Decreased semen quality and occasional azoospermia have also been found in heavy alcohol consumers (Guthauser, Boitrelle, Plat, Thiercelin, & Vialard, ).…”
Section: Discussionmentioning
confidence: 93%
“…Alcohol intake was found to modify free oestradiol and free testosterone ratio (Hansen et al, ), and to be consistently associated with spermatogenetic arrest and Sertoli‐cell‐only syndrome (Pajarinen et al, ). Recently, Silva et al () showed that cigarette and alcohol are associated with increased oxidative stress, and compromised epididymal and accessory sex glands functions. Additionally, ethanol has been shown to compromise sperm nuclear maturity and DNA integrity in rats (Talebi, Sarcheshmeh, Khalili, & Tabibnejad, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Declining human sperm quality has been demonstrated in several recent studies. Age, lifestyle, environmental pollutants and nutritional factors can affect semen quality [14, [50][51][52]. The present section focuses on studies of environmental exposure to EDCs and male reproductive function, as measured by declines in semen quality parameters or increased sperm DNA damage/fragmentation.…”
Section: Spermatozoamentioning
confidence: 99%